Efficacy of Role Play on Ill Effects of Alcoholism among College Going Students - Pooja R. Kasturkar1 , Prajakta Nandeshwar2 , Neha Mahabudhe2 , Priyanka Mohite2 , Priyanka More2 , S (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Alcoholism is the most serious type of substance addiction which includes drinking habitsand unable to control them. It is also called as Alcohol Dependence Syndrome or Alcohol use disorder.Aim: To determine the efficacy of role play on ill effect of alcoholism among college going student.Materials and Method: Purposive sampling was used to collect data from college going students by usingstructured knowledge questionnaire regarding ill effects of alcoholism with their selected demographicvariables.Results: The mean pre-test knowledge score was 12.27 and mean post-test knowledge score was 25.19.There was a statistically significant improvement in the level of knowledge regarding ill-effects of alcoholismamong college going students. The tabulated value for n=100-1 i.e. 99 degrees of freedom was 1.98. Thecalculated ‘t’ value i.e. 58.96 are much higher than the tabulated value at 5% level of significance foroverall knowledge score of college going students which is statistically acceptable level of significance andnoassociation was found between post-test knowledge score with their selected demographic variables.Conclusion: The demand of increase knowledge regarding ill effects of alcoholism is important amongcollege going students because they are more prone to consuming alcohol due to recreation, experience andspecially peer pressure